Partnering with communities to co-design humanitarian health strategie s: A SeeChange CommunityFirst Framework for implementation in MSF proj ects - Chapela Trillo, Violeta; Farber, Jessica (MSF, 2024)
The CommunityFirst Framework is intended to be implemented by field te ams at MSF. The theoretical aspects and evidence presented on the impo rtance of community engagement are intended for all MSF staff seeking to learn more about why and how to shift the way we work with communit ies as humanitarians. We believe this guideline, and other tools like it (including OCA’s Person-Centred Approach Guidance07, and MSF Vienna Evaluation Unit’s Guidance for Involving Communities08), to be an imp ortant contribution to the growing movement of communities and humanit arian actors who are pushing for changes in the humanitarian system th at translate to dignity, health, justice, equity and self-determinatio n for communities around the world. Specifically, the CommunityFirst F ramework is intended to guide MSF teams to co-design health strategies with communities, throughout all stages of the project cycle, for exp loratory missions, projects that are just opening, projects that have been running for some time, or those that are closing. At the time of publication, the CommunityFirst Framework has been tested in pilot pro jects in: (1) Madre de Dios, Peru (MSF OCP, August 2022), (2) Tonkolil i, Sierra Leone (MSF OCA, November 2022) and (3) Anzoátegui, Venezuela (MSF OCB, February 2023) The experiences from these pilots (feedback from teams, implementation results, adaptations to each context, etc.) have informed the adaptation of the Framework. CommunityFirst builds on existing community engagement work inside MSF and contributes a pra ctical framework for co-designing health initiatives with communities. To avoid duplicating efforts and resources around community engagemen t inside MSF, the appendices in this guideline largely refer to alread y existing MSF resources.09 This guideline is meant to be a living doc ument that can evolve and be adapted given the experience of MSF staff and community members and diverse community contexts. This guide can be used by anyone in MSF who is interested in partnering with communit ies to improve the responsiveness and impact of their humanitarian pro grams. This is the first iteration of the document. Subsequent iterati ons will be published based on additional testing during future phases of the CommunityFirst TIC project.